IMPLEMENTASI METODE DEMONSTRASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH BAB HAJI KELAS VIII MTS EL-JASMEEN SINGOSARI - Dina Solikhati; Mohammad Afifulloh; Adi Sudrajat (VICRATINA, 2022)
This research is motivated by conventional methods or lectures used by Fiqh subject teachers in the Hajj chapter which makes students' learning motivation weak. while the purpose of this study is to describe how the application of the demonstration method in increasing students' motivation to study fiqh subjects hajj chapter VIII MTs El-Jasmeen Singosari. This research in its implementation uses Classroom Action Research (CAR). The approach used is descriptive qualitative. The results of this study indicate that there is a significant increase in learning motivation. This can be proven through the results of the teacher activity observation sheet in the first cycle reaching a percentage of 69% which means that the success rate of implementing the demonstration method in the first cycle is in the Enough category and student learning activities reach a percentage of 57.5% which means it is in the category Enough. in cycle II the percentage of teacher activity increased by 89%, which means that the process of teaching and learning activities carried out by teachers was very good and according to the plans prepared before the implementation of cycle II. While the acquisition of the percentage of student learning activities is 90%, which means that student activities during learning activities by applying the demonstration method in cycle II are in the Very Good category. The results of the description on the student learning motivation observation sheet showed an increase in student learning motivation. With the implementation of the demonstration method, all students are more ready to accept fiqh learning, they are more interested in paying attention to the explanation of the learning material delivered by the teacher because the way of delivering learning is more interesting so that students can pay more attention directly to the learning steps through the learning media demonstrated in the Hajj chapter. Thus, based on the results of the study, it was shown that the implementation of the demonstration method could increase the learning motivation of eighth grade students of MTs El-Jasmeen Singosari.